If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 40 = 2x + 20 Reorder the terms: 40 + 3x = 2x + 20 Reorder the terms: 40 + 3x = 20 + 2x Solving 40 + 3x = 20 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 40 + 3x + -2x = 20 + 2x + -2x Combine like terms: 3x + -2x = 1x 40 + 1x = 20 + 2x + -2x Combine like terms: 2x + -2x = 0 40 + 1x = 20 + 0 40 + 1x = 20 Add '-40' to each side of the equation. 40 + -40 + 1x = 20 + -40 Combine like terms: 40 + -40 = 0 0 + 1x = 20 + -40 1x = 20 + -40 Combine like terms: 20 + -40 = -20 1x = -20 Divide each side by '1'. x = -20 Simplifying x = -20
| 1/3(x-9)1/8(3x-1) | | 4x^2-36x+72= | | 13i+7=2i-9 | | 594=18b+72 | | 2(x+2)=6x+1-4x+3 | | -6w+10=-10-8w | | x(5)=315 | | 2z+4z+2+z+10=z+2+20 | | 9y+5=15y+7 | | s^3+2s^2+12s-40=0 | | 120-80y=-3y+9 | | 4+4y+2=-2 | | 46/n=117 | | N^2-12n=32 | | 4a(5)3= | | 2x-5=2x+18 | | m-11=15-6b | | -6x+-6x= | | t=1.25h-10 | | -1-7x=36x+(-7-x) | | -6z+6=6-6z | | 0.2v=1.2 | | 2(y-1)+6y=10 | | 25-6x=-65 | | 7x-(3x+13)=23 | | 21-1/24(3)=14-1/24(2x) | | 1.1-t+2.2=5.9 | | 10x^3-9x^2-9x= | | 0=-6y+6y | | 2n=3(n+9) | | 21-1/24(3x)=14-(2x) | | (4a(5))3= |